Fracture Energy Estimation of DCB Specimens Made of Glass/Epoxy: An Experimental Study - V. Alfred Franklin; T. Christopher (Advances in Materials Science and Engineering)
This paper examines critical load and corresponding displacement of double cantilever beam (DCB) composite specimens made of glass/epoxy of three different layups. Experiments were conducted on these laminates, and the fracture energy, GIc, was evaluated considering the root rotation at the crack tip. The present model requires the applied load-displacement history and crack extension to estimate fracture energy. Reduction schemes based on cubic and power law are also proposed to determine Young’s modulus and energy release rate and found good agreement with the published and test results.